Impact of HIV/AIDS on deaths certified at Mosvold Hospital, Ingwavuma, Northern KwaZulu-Natal from January to August 2003 - C.H. Vaughan Williams (South African Family Practice)
An analysis of the causes of death certified at Mosvold Hospital, Ingwavuma demonstrates the impact of HIV/AIDS in the region. HIV/AIDS appears to be responsible for about 45% of registered deaths in both males and females after the age of nine years. There is a significant difference in the mean age at death between males and females succumbing to the disease after the age of nine years: the average age at death of females from HIV/AIDS is 35 years, and the average age for males is 40 years. The younger average age of death from HIV/AIDS in females, together with a higher expected age of death from non-HIV causes, means that females lose considerably more years of life due to HIV/AIDS than males. The figures for this part of northern KwaZulu-Natal indicate a higher impact of HIV/AIDS on deaths than in previous assessments for South Africa as a whole.